2020
DOI: 10.1063/5.0019188
|View full text |Cite
|
Sign up to set email alerts
|

Laminated low-melting-point-alloy electrodes for vacuum-free-processed quantum-dot light-emitting-diodes

Abstract: Quantum-dot light-emitting-diodes (QLEDs) can be fabricated by low-cost solution processes, such as spin-coating or inkjet printing, making them strong rivals to their organic LED counterparts. However, the top electrodes, which are usually based on metallic thin-films, such as Al or Ag, have to be deposited by a costly vacuum process, which is incompatible with the low-cost solution process. In this work, an InSnBi alloy, which has a low-melting-point of 47 °C, is developed as a laminated top cathode for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Figure a–e depicts the XPS spectra of Bi, In, Sn, and Pb elements. As can be seen in Figure b–d, the elemental XPS spectra of Bi, In, and Pb depict multiple peaks such as Bi 4f 7/2 , 4f 5/2 , 5s; In 3d 5/2 , 3d 3/2 ; and Pb 4f 7/2 , 4f 5/2 , respectively, which result from the spin–orbit interaction . Therefore, the Bi, In, and Pb elements in LMPA composition exist in the metallic state.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Figure a–e depicts the XPS spectra of Bi, In, Sn, and Pb elements. As can be seen in Figure b–d, the elemental XPS spectra of Bi, In, and Pb depict multiple peaks such as Bi 4f 7/2 , 4f 5/2 , 5s; In 3d 5/2 , 3d 3/2 ; and Pb 4f 7/2 , 4f 5/2 , respectively, which result from the spin–orbit interaction . Therefore, the Bi, In, and Pb elements in LMPA composition exist in the metallic state.…”
Section: Resultsmentioning
confidence: 89%
“…However, the XPS spectrum of Sn exhibits four peaks which are metallic 3d 5/2 , 3d 3/2 and oxidized 3d 5/2 , 3d 3/2 centered at 484.2, 492.4 eV and 485.85, 494.35 eV, respectively (Figure e). The presence of oxidized Sn 3d 5/2 and Sn 3d 3/2 indicate that a part of Sn is oxidized and forms SnO . Recently, Xia et al demonstrated that the presence of the native oxides in oxidized Sn could serve as an electron blocking layer in the quantum-dot light-emitting diodes (QLEDs), which improve the charge balance injection as well as stability of the devices. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations